Frontofacial Reconstruction Technique Modification With Preservation of Blood Supply to the Monobloc Segment. Issue 5 (27th July 2022) - King, Brody; Veith, Jacob; Kim, Erinn; Kestle, John; Siddiqi, Faizi; Gociman, Barbu
Abstract : Abstract: Craniosynostosis syndromes, including Apert Syndrome, Pfeiffer Syndrome, and Crouzon Syndrome, share similar phenotypes, including bicoronal craniosynostosis, midface hypoplasia, hypertelorism, and exorbitism. The standard surgical treatment for these craniofacial abnormalities is monobloc osteotomy with distraction osteogenesis. Complications of this technique include the failure of osteogenesis or resorption of the frontal bone. The authors propose an alternative surgical technique with a frontal arch in continuity with the midface segment to ensure vascularization to anterior and posterior borders of distraction. A case report of an 8-year-old female patient with Apert Syndrome is reported using our technique. Our frontal arch monobloc distraction procedure preserves blood supply to a cranial component of the monobloc segment site that becomes the anterior portion of distraction rather than with the traditional devascularized frontal bone flap. This technique modification should improve osteogenesis outcomes by preventing resorption or failure of bone formation.